Growth and Poverty Revisited from a Multidimensional Perspective. Issue 2 (1st February 2019) - Santos, Maria Emma; Dabus, Carlos; Delbianco, Fernando
Abstract: The actual impact of economic growth on poverty reduction is of fundamental importance to the development agenda. This paper offers new empirical evidence on growth and poverty measured from a multidimensional perspective using the global Multidimensional Poverty Index. Results from a First Difference Estimator Model suggest that while economic growth reduces multidimensional poverty, this impact is well below a one-to-one relationship and lower than the impact of growth on income poverty. Results from a cross-section model additionally suggest that countries with higher levels of exports, higher share of industry and services and higher control of corruption have lower multidimensional poverty.